Contextual and personal factor related to academic performance in high school students - María Luisa Avalos Latorre; Roberto Oropeza Tena; José Carlos Ramírez Cruz; Mónica Fulgencio Juárez (Revista de Psicología y Ciencias del Comportamiento de la Unidad Académica de Ciencias Jurídicas y Sociales, 2020)
The formal education is decisive in the development of an individual, nevertheless, to determine the factors that carry a suitable school performance turns out to be complex due to the fact that these are of diverse nature. The aim of this work was to relate and to compare the contextual and personal factors and the academic performance in students of high school. Participate 592 adolescence assigned to four high school of a public university of firstly, third and fifth semester. Each one answered a card of identification of personal, familiar and school information and there recovered his school global average of the system of school control. We observe significant differences between the academic performance and: sex, school shift, labor activity, school expectations, time of study and obtaining of academic, not like that recognitions with: marital status, school of adscription, to have children and education of the parents. We confirm the importance of the process of autoreference to evaluate the skills in relation with the goal the personal and context factors